Monetary Policy from An Islamic Perspective - Rahmat; M. Shabri Abd. Majid; M. Ridwan; Ade Khadijatul Z. Hrp (PT Inovasi Pratama Internasional, 2024)
Government as holder mandate demanded so that capable of managing economy , Good in scale micro or more broadly on a macro scale. . Policy monetary that is program government Which in matter This done by bank central through market Money in framework influence situation macro. Islamic monetary policy goals are no different with objective policy monetary conventional that is guard stability from eye Money (Good in a manner internal nor external) so that growth economy Which equally that can be expected achieved. Study This use method qualitative, namely by reviewing the literature from a number of study Which Already There is. To realize this goal of Islam not only have to do economic reform and society get along with stripes Islam, but also requires the positive role of government and all policy country including fiscal, monetary And income must in tune. Practices monopoly must be eliminated and every effort should be made to promote all factors Which able to produce increased goods and services.